2021
DOI: 10.1088/1361-6560/abde97
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated 3D image reconstruction with a morphological pyramid and noise-power convergence criterion

Abstract: Model-based iterative reconstruction (MBIR) for cone-beam CT (CBCT) offers better noise-resolution tradeoff and image quality than analytical methods for acquisition protocols with low x-ray dose or limited data, but with increased computational burden that poses a drawback to routine application in clinical scenarios. This work develops a comprehensive framework for acceleration of MBIR in the form of penalized weighted least squares optimized with ordered subsets separable quadratic surrogates. The optimizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 64 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…29,35,36,40 It is important to note that previous studies have demonstrated that the combination of the OS approach with momentum schemes can lead to convergence instability, particularly as the number of subsets increases. 47,48,58,59 This instability arises due to error accumulation in the momentum term, as the "subset balance" approximation does not perfectly hold. 47 The "subset balance" approximation implies that the cost function, JðFÞ, defined in Eq.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,35,36,40 It is important to note that previous studies have demonstrated that the combination of the OS approach with momentum schemes can lead to convergence instability, particularly as the number of subsets increases. 47,48,58,59 This instability arises due to error accumulation in the momentum term, as the "subset balance" approximation does not perfectly hold. 47 The "subset balance" approximation implies that the cost function, JðFÞ, defined in Eq.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Future refinements of the proposed method may explore the different strategies from the literature to obtain a provably convergent method. 48,58,59 Subsequent investigations may focus on evaluating the method's efficacy in imaging complex dynamic physiological processes and quantifying relevant parameters, such as wash-in and wash-out rates for tumor vascular perfusion. 37,60 These evaluations might encompass both in-vivo and in-silico experiments, further advancing the understanding and application of the proposed method.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The execution times are primarily affected by forward and back-projections of the volume (here, a total of 3 forward and 3 back-projections implemented per iteration) and the application of the spectral model. To address these bottlenecks, we are currently investigating: (i) multiresolution reconstruction that employs a finer voxel grid in the regions of interest (Cao et al 2016, Sisniega et al 2021, and (ii) polynomial approximation of the polyenergetic forward model (Abella et al 2019). Another important consideration for clinical translation is ensuring robust convergence of the algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The head was positioned with a 45° tilt along the z axis, aligning the central scan plane with a plane joining the posterior skull base with a frontal brain region. The x-ray source spectrum was simulated with the Spektr [10] TASMICS model for 100 kV (+2 mm Al, + 0.2 mm Cu added filtration). The detector model featured a flatpanel detector with a 250 mg/cm2 CsI:Tl scintillator.…”
Section: Simulation Setup For System Optimizationmentioning
confidence: 99%